Measuring the impact of CLIL on language skills: a CEFR-based approach for higher education - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Author/s Antonio José Jiménez-Muñoz Universidad de Oviedo, Spain   ABSTRACT Advocates of CLIL (Content and Language Integrated Learning) have extolled the virtues of this approach to fostering both content and language alike. However, the generalised and varied implementation of EMI (English as a Medium of Instruction) in universities worldwide has led many lecturers to question these claims. This paper presents a CEFR (Common European Framework)-based model for measuring the impact of EMI at the tertiary level, the aim being to provide further evidence of the progress made in language-learning in modules taught in a foreign language. Using questionnaires based on the revised and refined CEFR descriptors from EAQUALS (Evaluation and Accreditation of Quality in Language Services), students answer an initial self-assessment survey about their background and language skills, which is controlled by a final questionnaire targeting their perceived progress throughout their instruction. Designed from the ground up with the CEFR as a backdrop, this method can be easily tallied with objective assessment to uncover data about students' linguistic performance in CLIL contexts.